2009
DOI: 10.1117/1.3158994
|View full text |Cite
|
Sign up to set email alerts
|

Optical approach to the salivary pellicle

Abstract: The salivary pellicle plays an important role in oral physiology, yet noninvasive in situ characterization and mapping of this layer remains elusive. The goal of this study is to develop an optical approach for the real-time, noninvasive mapping and characterization of salivary pellicles using optical coherence tomography (OCT) and optical coherence microscopy (OCM). The long-term goals are to improve diagnostic capabilities in the oral cavity, gain a better understanding of physiological and pathological proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…Although some research has been reported in ophthalmologic, dermatologic, gastrointestinal, gynecological, cardiac, and other OCT applications, (27) the little research that has been reported in the oral cavity has focused predominantly on oral malignancy, periodontal disease, and caries (2832). Our preliminary data using OCT and a simulated GERD model in extracted teeth show early changes in enamel thickness due to chronic GERD that are potentially greater than 50 μm, whereas the variability of the technique between repeated measurements at maximum resolution levels is below 10% (33). In this study we used OCT to quantify tooth substance loss as well as changes in optical reflectance and absorbance of dental hard tissues as measures of demineralization before and after 3 weeks of esomeprazole (20 mg b.i.d.)…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Although some research has been reported in ophthalmologic, dermatologic, gastrointestinal, gynecological, cardiac, and other OCT applications, (27) the little research that has been reported in the oral cavity has focused predominantly on oral malignancy, periodontal disease, and caries (2832). Our preliminary data using OCT and a simulated GERD model in extracted teeth show early changes in enamel thickness due to chronic GERD that are potentially greater than 50 μm, whereas the variability of the technique between repeated measurements at maximum resolution levels is below 10% (33). In this study we used OCT to quantify tooth substance loss as well as changes in optical reflectance and absorbance of dental hard tissues as measures of demineralization before and after 3 weeks of esomeprazole (20 mg b.i.d.)…”
Section: Introductionmentioning
confidence: 83%
“…Two processes contribute to this phenomenon. First, back reflections occurring at the pore–enamel interfaces due to abrupt changes of the optical refractive index and, second, an effective reduction in scattering when light is traveling virtually without being deviated through the space inside the pores (33,40). This effect ensures that light coming from deeper regions within the sample reaches the OCT detection system.…”
Section: Discussionmentioning
confidence: 99%
“…In order to compare the results and to improve the resolution and specificity of images, an optical coherence microscope (OCM) was used. Salivary pellicle islands were visible in the samples incubated in saliva, which grow into complexes completely covering the enamel surface [ 43 ]. The aim of the next study was to evaluate the retention of the biofilm around orthodontic hooks depending on the ligaturing method using OCT and microbiological samples.…”
Section: The Short History Of Oct In Dentistrymentioning
confidence: 99%
“…Its primary mode of action is hypothesized to be through chemical desiccation or dehydration, leaving a denatured and destabilized biofilm which can then be removed by irrigation. In this pilot study, 3D Nonlinear Optical Microscopy imaging (NLOM) was used to generate non-contact high-resolution images of the biofilm and tooth surface [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%